Vascular endothelial growth factor (VEGF) and selected clinicopathological parameters in breast carcinoma - Litwiniuk, Maria; Łojko, Anna; Thielemann, Anna; Kopczyński, Zygmunt (Contemporary Oncology/Współczesna Onkologia, 2007)
Vascular endothelial growth factor (VEGF) is a key factor in normal and pathological angiogenesis. Increased levels of VEGF in cytosol, urine, serum, plasma or malignant tissue (mRNA) have been recorded in many tumour types, including breast cancer. The aim of this work was to determine the level of VEGF in the plasma of women with primary breast cancer and to find whether it was correlated with some clinicopathological parameters. The study group consisted of 104 women with primary breast cancer (stage I or II). The age of the women ranged from 29 to 89 years (average age – 57 years). For the assessment of VEGF concentration, venous blood was taken and immunoenzymatic (ELISA) method was used. The analysed clinicopathological variables included the size of the primary tumour, its histological type, the grade of histological malignancy and the status of axillary lymph nodes. The median concentration of VEGF in the study group was 95 pg/ml (3.5–490.2 pg/ml, SD 101.3). No correlation was found between the level of VEGF and the histological type of cancer or the patient’s age. The level of VEGF correlated significantly with the size of the primary tumour, the axillary node involvement and the grade of histological malignancy. The correlation found between the level of VEGF and some clinicopathological parameters indicates the important role that VEGF plays in tumour growth, and suggests a need for anti-VEGF therapy in breast cancer treatment.